Assessment of the Impact of Al-Dora Refinery and South-East Baghdad Electrical Power Generation Station on Air Quality at Al-Zafaraniya Region, Baghdad City - Muhannad K Mohammad (Journal of Global Pharma Technology, 2019)
In recent years, air contamination has become a serious environmental problem especially in industrialized and populated cities. Some activities such as random solid waste burning, industrial processes, local electrical generators, motor vehicles, fossil fuel combustion and other human activities can cause air pollution. The aim of current study was to evaluate the potential environmental impact of Al-Dora Refinery and South-East Baghdad Electrical Power Generation Station on ambient air quality. Methods: In this study, dust deposition rates were monitored on a weekly basis for the year 2017. Al-Zafaraniya region (residential area) in Baghdad city was selected as a monitoring point for measuring dust fallout rates and to evaluate the potential environmental impact of South-East Baghdad Electrical Power Generation Station (located about 3.2km to the north-west of the sampling point) and Al-Dora Refinery (located about 5.5km to the west of the sampling point) on ambient air quality. Results: Data revealed that the average amounts of dust fallout rates during this period were highly variable, ranged from 352.7kg/km2/month in January 2017 to 4348.8kg/km2/month in June 2017. Compared to permissible limits established in the literature, the annual total dust deposition rate observed in the monitoring point (23820.3kg/km2/year) was considered acceptable. The atmospheric concentrations of selected heavy metals including vanadium, chromium, manganese, copper, nickel, iron, cadmium, lead and zinc were measured using Flammable Atomic Absorption Spectrophotometer. The analysis results showed that cadmium had lowest concentrations among other investigated heavy metals with concentrations ranged from 0.22 to 2.61µg/m3, while zinc showed highest atmospheric concentrations (range from 132 to 410µg/m3). It was found that the mean atmospheric concentrations of lead, chromium, cadmium, copper and nickel were 6.15, 5.1, 1.2, 1.8 and 5.3μg/m³, respectively, exceeded the permissible limits. In contrast, zinc, manganese and vanadium in ambient air had acceptable mean concentrations (285.5, 2.5 and 10μg/m³, respectively) as compared to the corresponding permissible limits. Correlation coefficients between heavy metals concentrations were estimated to investigate potential relationships between atmospheric contaminants and to foretell the possible sources of heavy metals in air. The results showed strong positive correlation coefficients (>0%) between (Fe-Zn), (Fe-V), (Fe-Cd), (Cd-V), (Cu-V) and (Cu-Cd), indicating that these heavy metals have a high probability of being emitted from the same source of pollution.    Keywords: Dust fallout, Heavy metals, Permissible limits, Correlation coefficient, Baghdad city.